Differential timing of defense‐related responses induced by cerato‐platanin and cerato‐populin, two non‐catalytic fungal elicitors. Issue 3 (2nd April 2013) - Lombardi, Lara; Faoro, Franco; Luti, Simone; Baccelli, Ivan; Martellini, Federica; Bernardi, Rodolfo; Picciarelli, Piero; Scala, Aniello; Pazzagli, Luigia
<x xml:space="preserve">Abstract</x> The cerato‐platanin (CP) family consists of fungal‐secreted proteins involved in various stages of the host–fungus interaction and acting as phytotoxins and elicitors of defense responses. The founder member of this family is CP, a non‐catalytic protein with a six‐stranded double‐ψβ‐barrel fold. Cerato‐populin (Pop1) is an ortholog showing low sequence identity with CP. CP is secreted by Ceratocystis platani, the causal agent of the canker stain of plane. Pop1 is secreted by Ceratocystis populicola, a pathogen of poplar. CP and Pop1 have been suggested to act as PAMPs (pathogen‐associated molecular patterns) because they induce phytoalexin synthesis, transcription of defense‐related genes, restriction of conidia growth and cell death in various plants. Here, we treated plane leaves with CP or Pop1, and monitored defense responses to define the role of these elicitors in the plant interactions. Both CP and Pop1 were able to induce mitogen‐activated protein kinases (MAPKs) phosphorylation, production of reactive oxygen species and nitric oxide, and overexpression of defense related genes. The characteristic DNA fragmentation and the cytological features indicate that CP and Pop1 induce cell death by a mechanism of programmed cell death. Therefore, CP and Pop1 can be considered as two novel, non‐catalytic fungal PAMPs able to enhance primary defense. Of particular interest is the observation that CP showed faster activity compared to Pop1. The different timing in defense activation could potentially be due to the structural differences between CP and Pop1 (i.e. different hydrophobic index and different helix content) therefore constituting a starting point in unraveling their structure–function relationships.